2021
DOI: 10.1007/s10578-020-01079-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mental Health and Quality of Life Outcomes of Neonatal Insults in Kilifi, Kenya

Abstract: We examined the mental health and quality of life (QoL) outcomes and their correlates of school-aged survivors of neonatal jaundice (NNJ), hypoxic-ischemic encephalopathy (HIE), and a comparison group. The Child Behavior Checklist and the Pediatric Quality of Life Inventory were administered to assess the mental health and QoL of 375 children (134 with NNJ, 107 with HIE, and 134 comparison group) aged 6 to 12 years [Median age 9 (interquartile range 7 to 11)]. The results showed that survivors of NNJ and HIE h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Studies from other regions of SSA typically administered the ASEBA forms in one of the local languages (e.g., Swahili or Luo in Kenya). Two Kenya-based studies obtained official Swahili translations from ASEBA (Magai et al, 2018, 2021). At least one study from Uganda used the Luganda translation of the CBCL prepared by Bangirana and colleagues (2009).…”
Section: Resultsmentioning
confidence: 99%
“…Studies from other regions of SSA typically administered the ASEBA forms in one of the local languages (e.g., Swahili or Luo in Kenya). Two Kenya-based studies obtained official Swahili translations from ASEBA (Magai et al, 2018, 2021). At least one study from Uganda used the Luganda translation of the CBCL prepared by Bangirana and colleagues (2009).…”
Section: Resultsmentioning
confidence: 99%
“…Various studies have demonstrated an association between neonatal jaundice and neurological damage [ 35 , 36 ]. Several LMICS have also reported high rates of bilirubin-induced neurodevelopmental disorders and/or neurological impairments [ 37–39 ], which can subsequently manifest as behavioural or emotional problems [ 40 ]. A prospective cohort study carried out in Finland reported an association between hyperbilirubinemia and neurobehavioral problems such as attention deficit hyperactivity disorder (ADHD) in children [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other regions of SSA typically administered the ASEBA forms in one of the local languages (e.g., Swahili or Luo in Kenya). Two Kenya-based studies obtained official Swahili translations from ASEBA (Magai et al, 2021;Magai et al, 2018). At least one study from Uganda used the Luganda translation of the CBCL prepared by Bangirana et al (2009).…”
Section: Languages Of Administration Translations and Adaptationsmentioning
confidence: 99%